The molecular changing mechanism of Ampicillin-Sulbactam resistant Staphylococcus aureus towards Methicillin resistant Staphylococcus aureus - Mieke Hemiawati Satari (Dental Journal (Majalah Kedokteran Gigi), 2005)
The aim of this study was to determine the molecular changing of S.aureus, which is resistant to Ampicillin-Sulbactam and then become resistant to Methicillin as a result of improper dosage. The study was conducted by isolating Ampicillin-Sulbactam resistant and Methicillin Resistant S.aureus (MRSA), afterwards an amplification process was performed by PCR (Polymerase Chain Reaction.) to isolate the betalactamase enzyme regulator and PBP 2a genes. The result of this research showed that there were a deletion of few amino acids from the regulator gene, and a suspicion that the DNA sequence had been substituted from PBP 2 gene into PBP 2a (gen mec). This process had formed MRSA.